A dual functional Janus membrane combining superwettability with electrostatic force for controllable anionic/cationic emulsion separation and in situ surfactant removal. Issue 47 (25th November 2019) - Zhang, Weifeng; Qu, Ruixiang; Li, Xiangyu; Liu, Yanan; Wei, Yen; Feng, Lin
Abstract : A dual-functional Janus membrane was fabricated through mussel-inspired chemistry and an EDC/NHS coupling reaction for in situ oil-in-water emulsion separation and anionic/cationic surfactant removal with high efficiency. Abstract : In the oil/water emulsion treatment field, the separation of dispersed tiny oil droplets and the removal of surfactants are both significant in order to obtain purified water. Superwetting materials have proved to be an ideal solution for stabilized emulsion separation. However, most of the previous studies only focus on the separation of oil from water while neglecting the removal of surfactants. With the purpose of realizing in situ emulsion separation and surfactant removal, a dual functional Janus membrane is designed inspired by mussel-inspired chemistry and an EDC/NHS coupling reaction. After modification, abundant amino groups and carboxyl groups are decorated on two sides of the microfiltration membrane substrate, respectively (denoted as the –NH2 side and –COOH side). Combining special wettability with electrostatic interaction, the as-prepared membrane is able to separate stabilized oil-in-water emulsions and remove anionic/cationic surfactants simultaneously. The –NH2 side is used for the treatment of anionic emulsions with the surfactant sodium dodecyl sulfate (SDS), while the –COOH side is used for the treatment of cationic emulsions with the surfactant hexadecyl trimethyl ammonium bromide (CTAB). More importantly, the separation efficiencies are all above 99.5% and the surfactant removal efficiencies are up to 95.7%. To our knowledge, this is the first time to treat both dispersed oil droplets and surfactants using superwetting materials. The excellent recyclability and stability of the Janus material make it a potential candidate for application in the industrial field.